2017
DOI: 10.3390/app7090909
|View full text |Cite
|
Sign up to set email alerts
|

Laser Welding under Vacuum: A Review

Abstract: Laser welding has been widely used in various industry fields. In order to further alter and broaden its applicability, a novel technology of laser welding under vacuum is introduced. The combination of high power laser and low ambient pressure provides an excellent welding performance and quality. In this paper, an overview on laser welding under vacuum is presented. It begins with a short introduction about the research status of laser welding under vacuum. Next, the equipment of laser welding under vacuum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Aside from aluminium HPDC alloys different research on laser vacuum welding of a broad variety of materials have been carried out in the past [12]. Experimental research has shown that the vacuum has several influences on the welding process and its outcome: For example, the increase of penetration depth, the degeneration of the vapour plume and the decrease of weld spatter were shown by diffrent authors [13][14][15][16].…”
Section: Defects In Laser Welded Aluminium High Pressure Die Castingsmentioning
confidence: 99%
“…Aside from aluminium HPDC alloys different research on laser vacuum welding of a broad variety of materials have been carried out in the past [12]. Experimental research has shown that the vacuum has several influences on the welding process and its outcome: For example, the increase of penetration depth, the degeneration of the vapour plume and the decrease of weld spatter were shown by diffrent authors [13][14][15][16].…”
Section: Defects In Laser Welded Aluminium High Pressure Die Castingsmentioning
confidence: 99%
“…Shielding of the laser beam is reduced because the vapour generated by the process dissolves faster into vacuum. Consequently, vacuum enables an improved deep welding process with high aspect ratios due to the increased penetration depths Jiang et al (2017). These results can be transferred to thermally activated processes in general and give a first idea about the tendency of the following process behaviour.…”
Section: Additive Manufacturing Under Gravity and Vacuummentioning
confidence: 87%
“…The first one is a review paper from M. Jiang, W. Tao, and Y. Chen [11]. In this paper, a comprehensive overview on laser welding under vacuum is presented, which is a recently re-discovered laser welding technique [12] that can help in fully exploiting the potential of recently available high-power and high-brightness solid-state fiber and disk lasers.…”
Section: Solid State Lasers Materials Technologies and Applicationsmentioning
confidence: 99%